Severe Life Threatening Cardiovascular Complications Following Spinal Anaesthesia: A Case Series - Pantha, Sandesh; Basnet, NB; Piya, R; Shrestha, A; Baskota, D; Shrestha, G; Singh, RM; Subba, TN; Ghimire, B (Journal of General Practice and Emergency Medicine of Nepal, 2011)
Spinal anaesthesia, one of the safe and commonly given regional anaesthesias throughout the world1 was introduced by Dr August Bier in 1899. It is faster, easier to perform and patients are more comfortable than with general anaesthesia. Patan Hospital is one of the tertiary care referral hospital where many surgeries are performed every year. Obstetric, orthopaedic and general surgical cases are done under spinal anaesthesia in this hospital. We present here, a series of two life threatening complications following spinal anaesthesia in our patients who had undergone surgery under spinal anaesthesia.